Handle With Care: The Anterior Hip Capsule Plays a Key Role in Daily Hip Performance. Issue 3 (24th March 2022) - Duquesne, Kate; Pattyn, Christophe; Vanderstraeten, Barbara; Audenaert, Emmanuel A.
Background: Passive energy storage and return has long been recognized as one of the central mechanisms for minimizing the energy cost needed for terrestrial locomotion. Although the iliofemoral ligament (IFL) is the strongest ligament in the body, its potential role in energy-efficient walking remains unexplored. Purpose: To identify the contribution of the IFL to the amount of work performed by the hip muscles for normal, straight-level walking. Study Design: Controlled laboratory study. Methods: Straight-level walking of 50 healthy and injury-free adults was simulated using the AnyBody Modeling System. For each participant, the bone morphology and soft tissue properties were nonuniformly scaled. The superior and inferior parts of the IFL were represented by 2 springs each, and a linear force-strain relation was defined. A parameter study was conducted to account for the uncertainty surrounding the mechanical properties of the IFL. The work required from the gluteus, quadriceps, iliopsoas, and sartorius with and without inclusion of the IFL was calculated. Analysis of variance with subsequent post hoc paired t test was used to test the significance of IFL presence on the required mechanical work. Results: During walking, the strain in the IFL reached a median of 18.7% (95% CI, 8.0%-26.5%), with the largest values obtained at toe-off. With the IFL undamaged and fully operational, the effort required by the hip flexor muscles was reduced by a median of 54% (99% CI, 45%-62%) for the iliopsoas and by a median of 41% (99% CI, 27%-54%) for the sartorius muscles. The inclusion of the IFL did not significantly alter the work required by the gluteus and the quadriceps. Conclusion: The findings emphasized the key role the IFL plays in hip flexion by working synergistically with the hip musculature. Clinical Relevance: The importance of the contribution of the IFL to the hip flexors warrants careful handling and repair of these ligaments in cases of surgery and structural damage.